MEMBACA ALQURAN SEBAGAI HOMILI: Mendialogkan Antara Alquran Dan Bibel - Ulummudin Ulummudin; M. Zaid Su’di (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
This article examines a dialogue between Al-Qur’an and the Bible which have many similiarities particularly on the topic of stories. However, the studies on them have always been conducted separately, resulting in confusion among mufassirs when they try to understand the stories in the Qur’an based on the structure of the verses. In order to overcome this confusion, Gabriel Said Reynolds offers a method of reading Al-Qur’an as a homily. The Bible becomes the comparison and helps mufassirs to get detail information related to the same topics. One of the examples is the case of Sarah’s laughter. Mussafirs have different opinions on it because of the structure of verses written in the Qur’an. According to Gabriel Said, the problem would not appear if they wanted to study the Bible. The Bible states that Sarah’s laughter was caused by the good news about the birth of Isaac.